Analysis of polyvinyl alcohol microbubbles in human blood plasma using capillary electrophoresis. Issue 8 (29th March 2016) - Josefsson, Leila; Larsson, Malin K.; Bjällmark, Anna; Emmer, Åsa
Abstract : Recently, a new type of ultrasound contrast agent that consists of air‐filled microbubbles stabilized with a shell of polyvinyl alcohol was developed. When superparamagnetic nanoparticles of iron oxide are incorporated in the polymer shell, a multimodal contrast agent can be obtained. The biodistribution and elimination pathways of the polyvinyl alcohol microbubbles are essential to investigate, which is limited with today's techniques. The aim of the present study was, therefore, to develop a method for qualitative and quantitative analysis of microbubbles in biological samples using capillary electrophoresis with ultraviolet detection. The analysis parameters were optimized to a wavelength at 260 nm and pH of the background electrolyte ranging between 11.9 and 12. Studies with high‐intensity ultrasonication degraded microbubbles in water showed that degraded products and intact microbubbles could be distinguished, thus it was possible to quantify the intact microbubbles solely. Analysis of human blood plasma spiked with either plain microbubbles or microbubbles with nanoparticles demonstrated that it is possible to separate them from biological components like proteins in these kinds of samples.